BUILDING BUSINESS ADVANTAGE THROUGH CORE COMPETENCY: CASE STUDY PT. JAPFA COMFEED INDONESIA, Tbk. - Dian Addinna; Andreas Recki Prasetyo; Popy Rufaidah (Journal of International Conference Proceedings (JICP), 2018)
The purpose of this paper is to discuss the business advantages of a company engaged in the field of food through its core competency. This paper provides results of core competency analysis of PT. JapfaComfeed Indonesia, Tbk (JPFA). The research method used a case study that serves to express information in factual, structure, and accurate about the object study. The case study method used because it can improve the knowledge of what is already known through previous research. This paper used the information and data obtained from Annual Report JPFA 2016 and related records. This paper identifies a number of core competency factors based on finance performance analysis, business function analysis, and internal analysis & external factor summary (IFAS and EFAS). The based concept of the core competency refers to the Ljungquist (2007) model consists of capability, competence, and resource.The results of this paper show the core competency of JPFAin the capability of the company is able to produce products with good quality. In competence, the company is a market leader in its field by being able to dominate the market for animal feed products and DOC, synergy and efficiency in marketing product supported by the distribution network spread throughout Indonesia, and biosecurity such as isolation, fumigation, and farm management to guarantee quality of the product. In the resource, the company has professional and competent human resources. This paper provided managerial impact to company to maintain and develop business profits through its core competency. Keywords: Core Competency, PT. JapfaComfeed Indonesia, Tbk